Evaluasi Tata Kelola Teknologi Informasi Dinas Komunikasi, Informatika, Dan Statistik Kota Blitar Menggunakan Framework COBIT 4.1 Domain Plan and Organise (PO) dan Acquire and Implement (AI) - Fryda Rizkyta Ardiana; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
DISKOMINFOTIK is one of the government's agency that utilizes technological developments to improve services to public such as information systems, websites, and applications to support DISKOMINFOTIK operations. In its implementation, management deficiencies are still found there is no Standard Operation Procedure (SOP), investment management has not been well managed, doesn't have IT quality management, lack of resources to manage IT investments, its information systems are not updated regularly so that the growth of user needs is not fulfilled, there is no risk identification and risk management, there is no quality measurement regarding the implementation of current IT To get the results that are in conformable, it is necessary to evaluate IT governance to find out whether IT services are in accordance with the vision, mission and objectives and whether planning and implementation are well controlled. Evaluation is carried out so that the implementation of IT governance and runs optimally and in accordance with the expectations of managers of IT at DISKOMINFOTIK by using the COBIT framework 4.1 which focuses on the domain Plan and Organization (PO) and Acquire and Implement (AI). From the results of this study, it can be seen that the average maturity level for PO domains is 1.67 and the AI ​​domain is 1.00. It is necessary to increase the maturity level value to increase the current maturity level value as expected. Then given a number of recommendations that can be applied to DISKOMINFOTIK Blitar City. Some recommendations were generated, such as making SOP documents (Standard Operating Procedures) in all services in each field, training all IT staff to support existing IT processes, and defining and documenting risk management when implementing IT at DISKOMINFOTIK Blitar City.